Tal (bells): The sound of Rohi - Faiz, Farjad; Rasheed, Hira; Ansari, Maria (Pakistan Journal of Humanities and Social Sciences, 2024)
This research paper documents and discusses the process and the making of “Tal” special bells found in the region of Rohi, Southern Punjab, Pakistan. It is based on the research questions, research objectives were set in the context of Cholistan desert. To examine the craft of bells and it’s making process. The research identifies the social acceptance of bells and economic benefit for the artisan. Tal (Bell) is the unique craft of the desert of Cholistan. The sound of these bells is very fascinating in the quietness of desert. It creates the ambiance of peace, mystery, illusion and Sufism. When the whisper of the wind combines with the sound of bells create a pleasing sound. Bell is part of the cultural heritage of this region, but now it is vanishing due to increase in industrialization and rising demands of uniform perfection through mechanized production. There is thus a decline in the demand and acceptance of handmade crafts accompanied by apathy towards bell making as craft and its consequent significance as cultural heritage. The geographical area of the study was district Bahawalpur of Punjab, Pakistan. Qualitative research method has been used. Interview schedule was used as a tool to collect data from local artisans and their family members. It was a descriptive research study. The result indicates the preservation of the craft of bell making, and an archive of the sound of the bell should also be screated. Furthermore, there are many reasons to decline the craft of bell making.